A multi-site passive approach to studying the emissions and evolution of smoke from prescribed fires - R. El Asmar; Z. Li; D. J. Tanner; Y. Hu; S. O'Neill; L. G. Huey; M. T. Odman; R. J. Weber (Atmospheric Chemistry and Physics)
We conducted a 2-year study utilizing a network of fixed sites with sampling throughout an extended prescribed burning period to characterize the emissions and evolution of smoke from silvicultural prescribed burning at a military base in the southeastern USA. The measurement approach and an assessment of the instrument performance are described. Smoke sources, including those within and off the base, are identified, and plume ages are determined to quantify emissions and study the evolution of smoke PM2.5 (particulate matter with aerodynamic diameters 2.5 µm or smaller) mass, black carbon (BC), and brown carbon (BrC). Over the 2021 and 2022 prescribed burning seasons (nominally January to May), we identified 64 smoke events based on high levels of PM2.5 mass, BC, BrC, and carbon monoxide (CO), of which 61 were linked to a specific burning area. Smoke transport times were estimated in two ways: using the mean wind speed and the distance between the fire and the measurement site, and from Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) back-trajectories. PM2.5 emission ratios based on ΔPM2.5 mass /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="36bd7baae116a5efc17e692d563c2b51"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-12749-2024-ie00001.svg" width="8pt" height="14pt" src="acp-24-12749-2024-ie00001.png"/></svg:svg> ΔCO for fresh smoke (age ≤ 1 h) ranged between 0.04 and 0.18 µg m−3 ppb−1 with a mean of 0.117 µg m−3 ppb−1 (median of 0.121 µg m−3 ppb−1). Both the mean emission ratio and the variability were similar to findings from other prescribed fire studies but were lower than those from wildfires. The mean emission ratios of BC and BrC were 0.014 µg m−3 ppb−1 and 0.442 Mm−1 ppb−1, respectively. Ozone enhancements (ΔO3) were always observed in plumes detected in the afternoon. ΔPM2.5 mass /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="6e9042c80619a800f49fe8d9da77f107"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-12749-2024-ie00002.svg" width="8pt" height="14pt" src="acp-24-12749-2024-ie00002.png"/></svg:svg> ΔCO was observed to increase with plume age in all of the ozone-enhanced plumes, suggesting photochemical secondary aerosol formation. In contrast, ΔBrC/ΔCO was not found to vary with plume ages less than 8 h during photochemically active periods.